Women's experiences with implementation of the physiologic birth program in Iran: a qualitative content analysis study - Moridi, Azam; Abedi, Parvin; Iravani, Mina; Khosravi, Shahla; Alianmoghaddam, Narges; Maraghi, Elham; Saadati, Najmieh (Frontiers in Global Women's Health, 2023)
Introduction Increased rate of caesarean section (CS) without medical indication is a global concern. According to the guidelines of the World Health Organization (WHO), the physiologic birth program is one of the strategies for reducing the rate of unnecessary caesarean sections. The aim of this study is to explain women's experiences with the implementation of the physiologic birth program in Iran. Materials and methods This study is a part of a mixed-method study involving 15 targeted semi-structured interviews individually conducted with women attending physiologic birth classes between January 2022 and June 2022. Interviews continued until data saturation was achieved. Data were analyzed using conventional content analysis approach based on the criteria proposed by Graneheim and Lundman, using MAXQDA10 software. Results Analysis of the findings of the study led to the emergence of 2 themes, 4 categories, and 10 subcategories. The first theme was the positive experiences of the women (“satisfaction with pregnancy” and “making the childbirth process pleasant”), and the second theme was their negative experiences with physiologic birth (“challenges and limitation of physiologic birth program” and “lack of high-quality obstetric services in the public health system”). Conclusion The results of this study showed that childbirth preparation classes reduced women's fear and stress and enhanced their positive attitude toward vaginal delivery by preparing them for childbirth. Also, effective communication with midwives and their support along with efficient implementation of physiologic birth techniques led to successful pain management and satisfaction with the birth process. Policymakers should implement strategies to remove limitations and make this program accessible to all women.